Occupational Therapists' Perceived Relevance of Nussbaum's Central Capabilities to Client-centered Practice - Tahmineh Mousavi; Shafik Dharamsi; Susan Forwell; Elizabeth Dean (Scholarworks @ WMU, 2015)
Background: Client-centered practice is highly valued in occupational therapy. Nussbaum's Capabilities Approach focuses on the individual person and functional autonomy by encompassing 10 functional capabilities that could provide a framework for the systematic implementation of client-centered care. Method: To explore the perceived relevance of Nussbaum's 10 capabilities with respect to client-centered practice, semi-structured interviews with 14 occupational therapists in British Columbia, Canada, were conducted and thematically analyzed. Results: Nussbaum's Central Human Functional Capabilities approach provides a broad perspective, encompassing the range of settings of occupational therapy practice. Nussbaum's 10 capabilities were viewed as being particularly aligned with the established tenets of client-centered practice. Conclusion: Nussbaum's Capabilities Approach has several compelling attributes for consideration by occupational therapists that warrant further exploration as a novel basis for systematically implementing client-centered care.